Safety and Outcomes of Intravitreal Aflibercept in Diabetic Macular Edema – A Systematic Review - Dascalu, Ana M.; Rizzo, Manfredi; Rizvi, Ali A.; Stoian, Anca Pantea; Iancu, Raluca Claudia; Stana, Daniela; Tudosie, Mihail Silviu; Serban, Dragos (Current Pharmaceutical Design, 2022)
Background: Recent evidence on the role of vascular endothelial growth factor (VEGF) in the pathogenesis of ischemia and microvascular hyperpermeability leading to macular edema has brought anti-VEGF intravitreal therapy into the limelight. Objective: We performed a systematic literature review focusing on the outcomes and safety of the intravitreal use of aflibercept in diabetic macular edema. Methods: The studies documented cases with at least three consecutive intravitreal injections of aflibercept (IVA) repeated monthly with a follow-up period of at least one year. The outcomes were evaluated in terms of reported functional and anatomical improvement of the macula, as reflected by changes in visual acuity and macular thickness measured by Optical Coherence Tomography (OCT). In addition, for safety assessment, all reported local and general adverse effects were analyzed. Results: All studies showed an overall significant anatomical and functional improvement. In patients with the 5 IVA monthly at the beginning of the therapy, the visual gain at 52 weeks varied widely between 5 and 18.9 EDRS letters, with a mean value of 9.48 letters. The higher gain was obtained in treatment naïve patients, with worse VA and increased CST at baseline. The lower gain was obtained in patients previously treated with anti- VEGF. Anti-Platelet Trialists' Collaboration-defined arterial thromboembolic events were not statistically different between the aflibercept group and the laser group. Conclusion: Intravitreal aflibercept therapy provides significant improvement in visual acuity and a good safety profile. Randomized studies are needed to document the optimal frequency of intravitreal injections for optimal treatment.
Keywords: diabetic macular edema